Literature Study: Integration of Ethnophysics through Traditional Games in Sustainable Physics Learning - Mutiara Rizqi Hadi Ningrum; Nanda Nur Maulidiya Citra Dewi; Nina Fajriyah Citra; Joana Paula Gerabella da Costa Moniz (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study aims to examine the potential integration of ethnophysics through traditional games in sustainable physics learning. This approach is expected to produce learning that is interactive, conceptual, and relevant to local cultural values while answering the challenges in education in the modern era. Method: This research employs a descriptive approach, utilizing a systematic literature review method or literature study. Literature review research consists of several stages, including problem formulation, research, literature search, determination of inclusion and exclusion criteria, literature selection, data presentation, data processing, and conclusion. Results: The results demonstrated that this method was effective in enhancing students' understanding of physics concepts while preserving local culture. Traditional games are also considered relevant in facing learning challenges, such as low digital literacy skills and limited internet access. Additionally, this integration supports the Sustainable Development Goals, particularly in achieving quality education (SDG 4) and preserving local culture (SDG 11). Novelty: The uniqueness of this research lies in the combination of local wisdom values with physics learning, as it creates relevant, meaningful, and sustainable learning experiences. This research can also explore the integration of traditional games in physics education across various cultural contexts and educational levels. This combination offers an innovative approach that enhances conceptual understanding and reinforces local cultural identity.